HUBUNGAN ANTARA KEMAMPUAN KOGNITIF TENTANG ETIKA LINGKUNGAN, PERSEPSI TENTANG LINGKUNGAN DAN TANGGUNG JAWAB DALAM PELESTARIAN LINGKUNGAN DENGAN PERILAKU BERWAWASAN LINGKUNGAN - DARLIUS; J.P. SITANGGANG (Jurnal Satya Mandiri Manajemen dan Bisnis, 2015)
1. Cognitive abilities of environmental ethics and environmental behavior.2. The perception of the environmental and environmental behavior.3. Responsibility in the environmental conservation and environmental behavior.4. There is a positive correlation, between cognitive abilities of environmental ethics, perpection of the environment and responsibility in the environmental conservation and environmental behavior.